Therapeutic potential and nutraceutical profiling of North Bornean seaweeds: A review - Muhammad Dawood Shah; Balu Alagar Venmathi Maran; Sitti Raehanah Muhamad Shaleh; Wahidatul Husna Zuldin; Charles Gnanaraj; Yoong Soon Yong (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Malaysia has a long coastline surrounded by various islands, including North Borneo, that provide a suitable environment for the growth of diverse species of seaweeds. Some of the important North Bornean seaweed species are Kappaphycus alvarezii, Eucheuma denticulatum, Halymenia durvillaei (Rhodophyta), Caulerpa lentillifera, Caulerpa racemosa (Chlorophyta), Dictyota dichotoma and Sargassum polycystum (Ochrophyta). This review aims to highlight the therapeutic potential of North Bornean seaweeds and their nutraceutical profiling. North Bornean seaweeds have demonstrated anti-inflammatory, antioxidant, antimicrobial, anticancer, cardiovascular protective, neuroprotective, renal protective and hepatic protective potentials. The protective roles of the seaweeds might be due to the presence of a wide variety of nutraceuticals, including phthalic anhydride, 3,4-ethylenedioxythiophene, 2-pentylthiophene, furoic acid (K. alvarezii), eicosapentaenoic acid, palmitoleic acid, fucoxanthin, β-carotene (E. denticulatum), eucalyptol, oleic acid, dodecanal, pentadecane (H. durvillaei), canthaxanthin, oleic acid, pentadecanoic acid, eicosane (C. lentillifera), pseudoephedrine, palmitic acid, monocaprin (C. racemosa), dictyohydroperoxide, squalene, fucosterol, saringosterol (D. dichotoma), and lutein, neophytadiene, cholest-4-en-3-one and cis-vaccenic acid (S. polycystum). Extensive studies on the seaweed isolates are highly recommended to understand their bioactivity and mechanisms of action, while highlighting their commercialization potential.